A Green Hybrid Congestion Management Scheme for IoT-Enabled WSNs - Kaur G.; Chanak P.; Bhattacharya M. (My University, 2025)
In the modern era, the Internet of Things (IoT) plays a vital role in connecting physical objects to the Internet. Therefore, an IoT technology can monitor and control any physical object from remote locations. In IoT-based systems, Wireless Sensor Network (WSN) is used to monitor a large number of heterogeneous physical objects. The IoT-enabled WSNs suffer from congestion problems that significantly reduce the network lifetime and performance of the network. This paper present a green hybrid congestion control mechanism for IoT-enabled WSNs. It uses an unequal clustering mechanism which saves the energy of battery-limited sensor nodes and resolves energy hole issues. Furthermore, a novel two-class priority-based congestion avoidance mechanism is proposed which significantly reduces communication delay. Extensive simulations and real-life experiments are performed to demonstrate the effectiveness of the proposed scheme. Experimental result shows that the proposed scheme outperforms the state-of-the-art algorithms in terms of network lifetime, successful packet delivery, average throughput, and other parameters. Furthermore, the proposed scheme is also tested in a real testbed that demonstrates its effectiveness for disaster management in smart city applications. © 2017 IEEE.